Bank Sampah Sebagai Upaya Pemberdayaan Masyarakat - Reni Sri Hapsari; Eddy Suwasono; Ahsin Daroini (Universitas Islam Kadiri, 2020)
A waste bank is a place that is used to collect garbage that has been sorted. while Waste Bank Management uses a system such as Banking This study aims to find out about 1) General description of waste bank